Oil-in-water emulsion adjuvants for pediatric influenza vaccines: a systematic review and meta-analysis - Yu-Ju Lin (Nature Portfolio, 2020)
Here, the authors meta-analyze clinical trials comparing adjuvanted and non-adjuvanted influenza vaccines in children and find that oil-in-water emulsion adjuvant improves the efficacy of inactivated influenza vaccines in healthy immunologically naive children.